Pengembangan e-LKPD Berbasis CTL untuk Meningkatkan Sciences Process Skill pada Materi Suhu dan Kalor - Nisa Sa'diah; Andri Suherman; Rahmat Firman Septiyanto (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
In this study, we identified the feasibility and response of students to the development of CTL-based e-student worksheets, and after using the developed e-student worksheet. The purpose is to improve the capacity of scientific processes. An applicable research methodology is R&D using the ADDIE model. The research instrument used was an expert validation, a questionnaire for student, and pre-test post-test sheet. The developed electronic student worksheet was tested by 18 SMAN 1 Anyer Class XI students. Through the results of expert reviews conducted, student worksheets developed received an average material expert rating of 86.03% in the highly effective category and an average media expert rating of 86.75% in the highly effective category. Student responses averaged 85.8% in the very good category. The effectiveness of the student worksheets, evaluated using the results of the scientific process skills test and the pair sample test with an average n-gain score of 0.57 in the intermediate category, showed a significant difference between the students’s pre-test with post-test results. Therefore, it can be concluded that the CTL-based e-student worksheet has been declared viable and effective for enhancing scientific process capabilities related to temperature and thermal materials.